Therapeutic Effect of Umbilical Cord Blood and Placenta in the Treatment of Chronic Endometritis in Patients with Repeated Implantation Failures - Feskov, Oleksandr; Zhylkova, Yevhenia; Konoplia, Lina; Blazhko, Olena; Bezpechna, Iryna; Feskova, Anna (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):295